Implications of muscle strengthening on the function of the Triceps Sura venous pump in relation to the level of quality of life of people with Chronic Venous Insufficiency (CVI) (Research, Society and Development, 2024)
Physical training is an essential strategy in the management of patients with chronic venous insufficiency. This study aimed to evaluate the results of physical training on the function of the calf muscle pump, the functional features and the quality of life of these patients. Through an integrative review, new studies were developed that explored the topic. In cases of chronic venous insufficiency in the early stages, physical training has been shown to be effective in reducing venous reflux, increasing muscle strength, increasing ankle range of motion and improving patients' quality of life. On the other hand, in the advanced stages of the disease, physical training stood out for promoting increases in ejection fraction and reductions in residual volume fraction, in addition to improving muscle strength and ankle range of motion. However, no significant changes were observed in the rates of venous reflux in the ankle or in the quality of life of this population. It is concluded that physical training has positive effects on the function of the calf muscle pump, muscle strength and ankle range of motion in patients with chronic venous insufficiency. Furthermore, the benefits related to quality of life are more evident in individuals with current levels of the pathology.